TREATMENT OF PARATONSILLITIS IN CHILDREN WITH FLURBIPROPHEN IN CHILDREN - T.А. Polunina ("Paediatrician" Publishers LLC, 2011)
Inflammatory disorders of palatine tonsils are quite common in children. Usually complex treatment schemes of paratonsillitis include sprays, mouth rinses, soluble tablets and lozenges that contain various anti-inflammatory components. Their use decrease pain and duration of treatment, but doesn't exclude the use of systemic anti-inflammatory medications. Key words: pharyngitis, sore throat, flurbiprofen. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 143-145.)